Pengaruh Motivasi dan Lingkungan Terhadap Minat Berwirausaha : Studi Kasus Pada Mahasiswa STIMI Banjarmasin - Muhammad Hidayatullah; TA. Hariyono; Muhammad Nurdin; Dodik Jatmika (Edunomics Journal, 2025)
The purpose of this study was to determine the effect of motivation partially on the interest of STIMI Banjarmasin students in entrepreneurship, to determine the effect of the environment partially on the interest of STIMI Banjarmasin students in entrepreneurship, to determine the effect of motivation and the environment simultaneously on the interest of STIMI Banjarmasin students in entrepreneurship. This study uses a quantitative research method. The population in this study were STIMI Banjarmasin undergraduate students in the 2020-2023 intake. The sample in the study was taken based on the simple random sampling technique using the Slovin Formula with a leeway of 10% so that a sample of 59 people was obtained as respondents in this study. The analysis method uses Multiple Linear Regression Analysis to determine the effect between variables. Hypothesis Testing is used to determine the actual situation at the population level based on statistical data. Based on the results of this study, it is known that Motivation partially has a significant effect on the Entrepreneurial Interest, the Environment partially has a significant effect on the Entrepreneurial Interest, Motivation and Environment simultaneously have a significant effect on the Entrepreneurial Interest.